Psychopathology, cortisol and testosterone responses to traumatic images: differences between urban and suburban citizens in a middle-income country - Mayagoitia-Novales, Lilian; Cerda-Molina, Ana Lilia; Mendoza-Mojica, Sheila Adriana; Borráz-León, Javier I.; Hernández-Melesio, M. Alejandra; Saldívar-Hernández, Gabriela Josefina (Frontiers in Psychology, 2023)
Background: Living in urban places has been associated with a higher risk of psychopathology as well as with altered hypothalamus-pituitary-adrenal (HPA) axis and consequently altered cortisol response, but studies have concentrated mainly in high-income countries population. The role of other hormones such as testosterone, implicated in stress response and with human social behaviors, have not yet been investigated. The aim of this study was to compare symptoms of psychopathology as well as cortisol and testosterone in response to traumatic images between urban and suburban people in a middle-income country. Methods: A sample of 67 women and 55 men (N = 122, 18-45 years) from urban and suburban places of Mexico participated in the study. We quantified salivary cortisol and testosterone in response to images with traumatic and violent content (basal, 15, 30 and 45 min after images). Participants answered a general information questionnaire and the Symptom Checklist-90-R to assess their psychopathological traits. We performed Generalized Estimating Equation Models to analyze hormonal levels and MANOVAs to compare differences in participants' psychopathology symptoms. Area under the curve respect to ground (AUCG) of hormonal levels and sex differences were also compared. Results: Suburban citizens showed no cortisol response, whereas urban people showed a cortisol peak 15 minutes after the image's exposure; however, suburban people had higher AUCG and basal This is a provisional file, not the final typeset article levels compared to urban ones. Contrastingly, testosterone levels declined in all participants excepting the urban women, who showed no testosterone response. Although similar testosterone profile, AUCG levels were higher in urban than suburban men. Participants living in suburban areas had higher scores of somatizations, obsessive-compulsive, and interpersonal sensitivity, as well as more sleep disorders than participants living in urban areas.This study offers novel evidence about differences in cortisol and testosterone responses to a social stressor and in mental health indicators between a population of urban and suburban citizens, highlighting the impact of urbanization process on physiological and psychological outcomes in a middle-income country.